Clinical Evaluation of Cingulum Bundle Connectivity for Neurosurgical Hypothesis Development. Issue 5 (2nd July 2019) - Sweet, Jennifer A; Beylergil, Sinem Balta; Thyagaraj, Suraj; Herring, Eric Z; Drapekin, Jesse E; Gao, Keming; Calabrese, Joseph R; Miller, Jonathan P; McIntyre, Cameron C
Abstract: BACKGROUND: The cingulum bundle (CB) has long been a target for psychiatric neurosurgical procedures, but with limited understanding of the brain networks being impacted. Recent advances in human tractography could provide a foundation to better understand the effects of neurosurgical interventions on the CB; however, the reliability of tractography remains in question. OBJECTIVE: To evaluate the ability of different tractography techniques, derived from typical, human diffusion-weighted imaging (DWI) data, to characterize CB connectivity described in animal models. This will help validate the clinical applicability of tractography, and generate insight on current and future neurosurgical targets for psychiatric disorders. METHODS: Connectivity of the CB in 15 healthy human subjects was evaluated using DWI-based tractography, and compared to tract-tracing findings from nonhuman primates. Brain regions of interest were defined to coincide with the animal model. Tractography was performed using 3 techniques (FSL probabilistic, Camino probabilistic, and Camino deterministic). Differences in connectivity were assessed, and the CB segment with the greatest connectivity was determined. RESULTS: Each tractography technique successfully reproduced the animal tracing model with a mean accuracy of 72% (68-75%, P  < .05). Additionally, one region of the CB, the rostral dorsal segment, had significantly greater connectivity to associated brain structures than all other CB segments ( P  < .05). CONCLUSION: Noninvasive, in vivo human analysis of the CB, using clinically available DWI for tractography, consistently reproduced the results of an animal tract-tracing model. This suggests that tractography of the CB can be used for clinical applications, which may aid in neurosurgical targeting for psychiatric disorders.